ADVERTISING AND PURCHASE DECISION IN THE SHOPEE MARKETPLACE: Impact on Student e-Satisfaction - Surya Darni; Azhari Azhari; Sutan Febriansyah (J-MIND (Jurnal Manajemen Indonesia), 2023)
This study aimed to examine the effect of advertising on purchase decisions and the e-satisfaction of Students at the University of Bumi Persada Lhokseumawe, and examined the mediating effect of purchase decision. The sampling method used was purposive sampling and respondents were collected by distributing structured questionnaires to 120 respondents who had shopped at the Shopee marketplace. the data analysis method used is path analysis using Multiple Linear Regression with the help of SPSS Software. The results showed that advertising had a positive and significant effect on e-satisfaction and the purchase decision mediated between the advertising variable and the e-satisfaction. This has implications for enriching knowledge and theory on e-satisfaction and digital marketing.